2008
DOI: 10.1111/j.1365-2435.2008.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Weapon size is a reliable indicator of strength and social dominance in female slender crayfish (Cherax dispar)

Abstract: Summary 1.Weapons are specialized structures that are commonly used by animals to signal fighting ability and resource holding potential during agonistic encounters. Current theory predicts weapon size should reliably indicate weapon strength and unreliable signals should only occur at very low frequencies in nature. However, a recent study found weapon size was an unreliable signal of strength during agonistic interactions among males of the slender crayfish ( Cherax dispar ). 2. In this study, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 38 publications
5
34
0
Order By: Relevance
“…similar to that previously reported for C. dispar (males, CV75%; females, CV31%) Bywater et al, 2008). It is this variation between signal and an individual's actual performance (or potential to inflict a cost on an opponent) that forms the basis or opportunity for unreliable signals of strength to be used to determine dominance.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…similar to that previously reported for C. dispar (males, CV75%; females, CV31%) Bywater et al, 2008). It is this variation between signal and an individual's actual performance (or potential to inflict a cost on an opponent) that forms the basis or opportunity for unreliable signals of strength to be used to determine dominance.…”
Section: Discussionsupporting
confidence: 64%
“…Despite such theoretical expectations, there are many reported cases of unreliable signals of both fighting ability and mate choice across a range of species, including fiddler crabs (Backwell et al, 2000;Lailvaux et al, 2009), hermit crabs (Elwood et al, 2006), snapping shrimp (Hughes, 2000), stomatopods (Steger and Caldwell, 1983;Adams and Caldwell, 1990) and freshwater crayfish (Seebacher and Wilson, 2006;Wilson et al, 2007). Moreover, recent studies of male slender crayfish, Cherax dispar, revealed dishonest signals are routinely used during agonistic interactions and are far more common than previously predicted Bywater et al, 2008). In this system, male slender crayfish use relative chela size to determine dominance , but chela size is a poor predictor of chela strength (a measure of fighting ability), and strength is unrelated to social dominance .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous analyses have focused on either the properties of individual chelae or the average properties of paired chelae [15,20,21,22], ignoring the role of asymmetry in dominance. These analyses indicated that stronger individuals were more likely to win disputes that escalated into fighting.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce these potential costs animals often seek to resolve disputes without fighting by signalling intent, and using assessments of weapon size, body mass and/or aggressive displays (Bywater et al, 2008;Smith and Harper, 1995). Visual signals, and the intrinsic quality they represent, are used by receivers to assess the likelihood of combat success should physical confrontation ensue (Bradbury and Vehrencamp, 2011;Hughes, 2000).…”
Section: Introductionmentioning
confidence: 99%